The impact of different language policies to teach maths and science on language choices of UiTM Sarawak's diploma in science students / Caesar Dealwis ... [et al.] - Dealwis, Caesar; Johari, Aiza; Faizal Hakim, Simon Botley (2011)
This sociolinguistic study focuses on the younger generation of multilingual Malaysian tertiary students who have been exposed to different mediums of instruction when studying Science and Mathematics at school before joining UiTM. This study is limited to two domains, namely friendship and study, because these are the domains where the impact of the different language policies could be more obvious in influencing the language choices of the students.Even though there has been both positive and negative feedback on the policy of using English to teach Science and Mathematics which was implemented in 2001, the sociolinguistic aspect of it has hardly been studied. There is no information as to whether the different mediums of instruction have affected the language choices of these students once they pursue tertiary education. The Diploma in Science students at UiTM Samarahan, Sarawak best represent these two cohorts of students . Parts 1 2 and 3 have been exposed to the learning of Science and Mathematics in English when they were at school, since Form l. Parts 4, 5 and 6 have been exposed to the learning of Science and Mathematics in Bahasa Malaysia at school since Year 1. Being exposed to two separate medium of instructions could possibly have affected the language choices of students who pursed Diploma in Science at UiTM where the medium of instruction is in English.